Endoscopic sinus surgery: experience of 60 cases (Bangladesh Journal of Otorhinolaryngology, 2011)
Objective: To study the quality of life in patient who underwent ESS operation. Design and setting: A prospective study conducted over a period of one(01) year; from July 2004 to June 2005 in Otolaryngology – Head & Neck Surgery Department of Shaheed Suhrawardy Medical College Hospital and Dhaka Medical College Hospital, Dhaka, Bangladesh. Results: Hospital admitted 60(Sixty) cases of ESS patients were included and analyzed. 42 cases were male; whereas 18 cases were female in this study. 21-40 years (44 cases) were the commonest age group of study people. No significant/ alarming complications were recorded during post operative period. Conclusion: Instead of all limitations, outcome of ESS is more acceptable in comparison with conventional sinus surgery. The main symptoms, like nasal obstruction, discharge, headache and facial pain get relieved off dramatically which is compatible with other recognized study. Key words: Endoscopic sinus surgery; open the sinuses; restore normal air flow. DOI: http://dx.doi.org/10.3329/bjo.v17i2.8849 BJO 2011; 17(2): 104-109